ITIL V3 Foundation Exam - Knapp, Jill (Video mentor., 2011)
The ITIL V3 Foundation Exam Video Mentor is a combined book and DVD set which contains hours of instructor-led presentations in an easy-to-follow format, providing both foundational reinforcement of exam topics as well as exam preparation tips, tricks, and sample questions. The DVD video tackles each ITIL V3 Foundation topical area with the key concepts, process activities, roles, and vocabulary necessary to pass the ITIL V3 Foundation Exam based on the newest APMG syllabus, all through a fun and thorough teaching style. This ITIL V3 Foundation Exam Video Mentor set provides a test-preparation learning experience from a leading Certified ITIL Expert based on the latest examination syllabus, ensuring all current exam topics are covered. Don't be left behind by using outdated 2009-edition materials; this ITIL V3 Foundation Exam Video Mentor will help ensure your success!